Prímá revaskularizace myokardu z anterolaterální minitorakotomie - Hájek, T; Jirásek, K; Hlavácek, K; Cvachovec, K (Rozhledy v chirurgii, 1998)
The authors present the case of successfully treated patient with CAD, operated from left anterolateral minithoracotomy. Angiographic control two years later presents fully patent anastomosis without any signs of stenosis.
Keywords: torakotomie; revaskularizace myokardu; mužské pohlaví; Myocardial Revascularization; Thoracotomy; lidé; Male; miniinvazivní chirurgické výkony; Middle Aged; lidé středního věku; Minimally Invasive Surgical Procedures; Humans